Acetophenone - benzaldehyde ethylenediamine modified electrodes for the determination of metal ions in aqueous solutions - Azhari, Syaza (2017)
Concern over the harmful effect of toxic metals in the environment warrants the need of continuous improvement for their determination. Conventional methods such as inductively coupled plasma-mass spectrometry (ICP-MS) and atomic absorption spectrophotometry (AAS) for the determination of metal ions in aqueous solution have several drawbacks such as time consuming manipulation steps, need for sophisticated instruments and high maintenance costs. Alternative methods such as electrochemical technique have been suggested, particularly offering advantages in terms of speed of analysis, low cost, easy operation and ability to directly determine metal ion in complex aqueous samples. In the present study, acetophenone-benzaldehyde ethylenediamine compounds, N,N’-bis(2-hydroxyacetophenone)ethylenediamine, bis(4-hydroxybenzaldehyde)ethylenediamine, bis (benzylidene)ethylenediamine and N,N’-bis(2-hydroxy-4-methoxyacetophenone)ethylenediamine were synthesized and applied to modify carbon based electrodes for the determination of metal ions using electrochemical techniques. The ligands were used in-situ to enhance the detection of cadmium (Cd(II)) and copper (Cu(II)) ions using differential pulse anodic stripping voltammetry (DPASV). Under the optimized conditions the proposed in-situ DPASV method for Cd(II) and Cu(II) provides good limits of detection (LOD) and limit of quantification (LOQ) in the range of 0.1 - 1.0 µg L-1 and 1.30 - 4.53 µg L-1 respectively. The relative recoveries obtained for Cd(II) and Cu(II) in tap water and sea water samples were in the range of 82 - 118%. A composite carbon paste electrode modified with bis(benzylidene)ethylenediamine was successfully fabricated for the determination of Cd(II) using square wave anodic stripping voltammetric technique. The response surface methodological approach employing the Box-Behnken design was utilized to optimize the experimental conditions for the detection of Cd(II). Under optimized conditions, a linear response over a wide range of Cd(II) concentrations (1–500 µg L-1) with low LOD (0.4 µg L-1) and LOQ (1.4 µg L-1) were observed. The electrode employed in this styudy exhibited exceptional recovery results over a wide range of Cd(II) concentrations in the sea and tap water samples. A modified electrode consisting of multi-walled carbon nanotubes (MWCNT), 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim]PF6), N,N’-bis(2-hydroxy acetophenone)ethylenediamine and Nafion was developed on glassy carbon electrode to investigate the electrochemical behaviour and direct determination of silver (Ag(I)) ion using cyclic voltammetry and DPASV. Under optimized conditions, the DPASV calibrations were linear in the range of 0.2 to 200 µg L-1. The LOD and LOQ obtained were 0.07 µg L-1 and 0.2 µg L-1 respectively. Repetitive measurements revealed good reproducibility with a relative standard deviation value of 0.4%. To prove the applicability of the proposed modified electrode, 10 stations of the river water samples were collected between Malaysia-Singapore Second Link and the Causeway along the Johor Straits and the Ag(I) content was analysed using the developed method. The results were compared to the standard method and were found to be superior to those of conventional methods that have been reported in previous work.